Quest, chaos and restitution: a qualitative study of the experiences of individuals diagnosed with fibromyalgia syndrome - Diver, Claire J. (2012)
Purpose: To describe the experiences of individuals recently diagnosed with fibromyalgia syndrome (FMS) using Arthur Frank's narrative typologies.